2015 Kansas Performance Tests with Corn Hybrids - Lingenfelser, Jane (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2017)
Corn performance tests, conducted annually by the Kansas Agricultural Experiment Station, provide farmers, extension workers, and seed industry personnel with unbiased agronomic information on many of the corn hybrids marketed in the state. Entry fees from private seed companies finance the tests. Because entry selection and location are voluntary, not all hybrids grown in the state are included in tests, and the same group of hybrids is not grown uniformly at all test locations. Most companies submit seed treated with systemic insecticides, which can affect yield in some situations. Contributors: Main Station, Manhattan: Jane Lingenfelser, Assistant Agronomist (Senior Author); Doug Jardine, Extension Plant Pathologist; Mary Knapp, KSU Weather Data Librarian; Edward O. Quigley, Agricultural Technician; Holly Schwarting, Extension Entomologist; Brent Christenson, Agronomy; Experiment Fields: Eric Adee, Topeka; Gary Cramer, Hutchinson; Andrew Esser, Scandia; Jim Kimball, Ottawa; Keith Thompson, Hutchinson; Research Centers: Patrick Evans, Colby; Lonnie Mengarelli, Parsons; Gerald Rohleder, Hays; Alan Schlegel, Tribune; Monty Spangler, Garden City; Cooperators: D.J. Eidman, Strong City; Fuhrman Farms, Severance; Rezac Farms, Onaga; Clayton Short, Assaria; Mark and Aaron Vogts, Moundridge; Justin Vosburgh, Macksville.
Keywords: Corn; Yields; Kansas; Disease; Weather